Radiofrequency ablation with sine and square electrical waveforms to enhance ablation range - Won, Dong-Sung; An, Jinsu; Kim, Ji Won; Park, Yubeen; Lee, Sang Soo; Kim, Hyung-Sik; Park, Jung-Hoon (Frontiers in Bioengineering and Biotechnology, 2024)
Radiofrequency ablation (RFA) is a local treatment modality for primary liver cancers. Although various input parameters of the RF generator have been adjusted to improve the ablation ranges, the limited ablation ranges remain an obstacle to RFA. This study aimed to compare the ablation ranges and efficacy of sine and square electrical waveforms in a mouse tumor model. An RF generator with an adjustable electrical waveform was developed, and its ablation range in the porcine liver was compared. For all RF parameters, the square electrical waveform ablation range was greater than that of the sine electrical waveform (all p < 0.001) in the porcine liver. The 45 BALB/c nude mice were used to evaluate the efficacy of the two electrical waveforms after the RFA. The mean tumor volume in the square group was significantly lower than that in the sine group (p < 0.001), indicating a higher survival rate (60%). The cellular coagulative necrosis, inflammatory cell infiltration, heat shock proteins, cellular necrosis, and tumor necrosis were significantly greater in square electrical waveform than in sine electrical waveform (all; p < 0.05). RFA with square electrical waveforms has therapeutic potential for tumor management with an enhanced ablation range.